'The First Cut is the Deepest': Excerpts from a Focus Group on Editing Music Videos, with Explanatory Historical and Theoretical Notes. Issue 1 (July 2017) - Caston, Emily
Abstract : It is often said that one of the lasting impacts of music videos is the fast 'MTV edit' in mainstream narrative film. In this edited collection of excerpts from a focus group on music videos, British music video editors challenge the idea that the fast edit was the sole overriding concern, and talk about the impact of changing editing technologies, aesthetics and commercial practicalities on their craft. The editors participating in the group included: Tony Kearns who, between 1989 and 2005, edited iconic videos for The Prodigy, Radiohead, Blur, Paul Weller, Suede, Chemical Brothers, Coldplay, Manic Street Preachers, and Pulp, amongst others; Art Jones, whose credits include Adele, Armand Van Helden, Kaiser Chiefs, Stereophonics, Feeder, Moloko, and The Streets; Tom Lindsay who has cut videos for Will Young, Kasabian, Franz Ferdinand, the Arctic Monkeys, and The Shoes' 'Time To Dance'; director Dawn Shadforth who has directed videos for Oasis, Kylie Minogue, Moloko, All Seeing I, The Streets, Goldfrapp, and Jamiroquai; Julia Knight who has cut videos for Dizzee Rascal, Coldplay, Arctic Monkeys, and FKA Twigs; and Adam Dunlop ex-Head of Music Video at the Oil Factory, ex-Director of Music Video at Sony Music 1999–2003, and subsequently an editor at Swordfish. This article was published open access under a CC BY licensehttps://creativecommons.org/licenses/by/4.0/